2007
DOI: 10.1007/s00417-007-0589-2
|View full text |Cite
|
Sign up to set email alerts
|

Perimetric and retrobulbar blood flow changes following carotid endarterectomy

Abstract: Perimetric changes occur in carotid stenosis. CEA results in the improvement of retrobulbar blood flow and perimetric parameters. Further research will be required to determine whether perimetric parameters may be used as additional indicators for carotid endarterectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
18
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 30 publications
2
18
0
Order By: Relevance
“…The perimetric median defect also bilaterally improved, thus supporting the above hypothesis of OBF in one eye influencing the fellow eye (Kozobolis, 2007).…”
Section: A Sick Eye In a Sick Bodysupporting
confidence: 77%
“…The perimetric median defect also bilaterally improved, thus supporting the above hypothesis of OBF in one eye influencing the fellow eye (Kozobolis, 2007).…”
Section: A Sick Eye In a Sick Bodysupporting
confidence: 77%
“…Several studies have demonstrated the restoration of cerebral blood flow in ipsilateral cerebral hemisphere following CEA surgery in short-and long-term follow-ups 28,29 ; however, recent studies have also reported a blood flow redistribution phenomena through the collateral circulation, that is, via the circle of Willis and ophthalmic arteries, following CEA. 30 Functional and efficient blood supply to the contralateral cerebral hemisphere via the circle of Willis leads to an improved cerebrovascular reserve in both cerebral hemispheres. Wang et al be included in future randomized controlled trials investigating the final biological outcomes of CEA in patients with different stages of carotid artery disease.…”
Section: Discussionmentioning
confidence: 99%
“…15,16 Consequently, ICA surgery for stenosis effectively improves hemodynamic parameters both in the central retinal artery and short posterior ciliary arteries in patients with acute and chronic forms of ocular ischemic syndrome in the postoperative period. 17,18 Therefore, CEA may reduce or prevent the progression of chronic ocular ischemia and improve hypotensive retinopathy, as well as remove the risk of plaque-related embolization. Functional ocular improvement following CEA has been documented by several previous studies that have examined various parameters, including visual acuity, 18 To characterize factors that may influence the results obtained from complex ERG testing, we evaluated the potential association between the changes in full-field ERG amplitudes and several systemic risk factors and metabolic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Ophthalmologists have found results suggesting visual acuity improvement from the procedure. [11][12][13] At the same time, studies have reported negative effects of CEA on visual acuity. 14 No data have been published concerning the effect of CEA on hearing ability.…”
mentioning
confidence: 95%